2018
DOI: 10.1530/joe-17-0642
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol ameliorates androgen-induced behavioral deficits in developing male rats

Abstract: The purpose of present study was to infer the potential effects of testosterone increase in some male-based childhood-onset neuropsychiatric disorders, such as Tourette syndrome. Thus, the influence of early postnatal androgen exposure upon the neurobehaviors and its possible neural basis were investigated in the study. Male pup rats received consecutive 14-day testosterone propionate (TP) subcutaneous injection from postnatal day (PND) 7. The TP treatment produced the hyperactive motor behavior and grooming b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…Tyrosine hydroxylase (TH) is the rate-limiting enzyme in catecholamine biosynthesis in the brain and is responsible for the conversion of L -tyrosine to 3,4 dihydrophenylalanine (DOPA) (Brett et al, 1995; Zhu et al, 2012; Tekin et al, 2014). Dysregulation of TH activity is essential in the pathogenesis of TS (Brett et al, 1995; Comings et al, 1995; Qi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Tyrosine hydroxylase (TH) is the rate-limiting enzyme in catecholamine biosynthesis in the brain and is responsible for the conversion of L -tyrosine to 3,4 dihydrophenylalanine (DOPA) (Brett et al, 1995; Zhu et al, 2012; Tekin et al, 2014). Dysregulation of TH activity is essential in the pathogenesis of TS (Brett et al, 1995; Comings et al, 1995; Qi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Activated AR can increase Th promoter activity in cell lines ( 49 ). In several studies in adolescent male rats androgens where shown to stimulate TH and S lc6a3 mRNA or protein expression ( 50 53 ). The discrepancies between these observations and the results obtained by us and others could be influenced by either the age of the animals or possibly by a species difference between mice and rats.…”
Section: Discussionmentioning
confidence: 99%
“…There is information indicating that postnatal increases in testosterone levels under certain conditions may trigger pathways resulting in adverse outcomes, although the relevance of these findings for experimental postnatal studies with phthalates is unclear. Examples cover experimental, human and epidemiological studies associating testosterone increase with neurological and neurodevelopmental effects (Qi et al., 2018; Nakano et al., 2010; Hines, 2003; Schwarz et al., 2011) and apical effects associated with overexpression of androgens (Hotchkiss et al., 2007; Martin et al., 1998). There are also some epidemiological studies linking phthalate exposure with metabolomic alterations (Zhou et al., 2018, neurodevelopmental Braun, 2017, Engel et al., 2018) and effects attributable to hyperandrogenism (Colon et al., 2000).…”
Section: Assessmentmentioning
confidence: 99%
“…There is information indicating that postnatal increases in testosterone levels under certain conditions may trigger pathways resulting in adverse outcomes. Examples cover experimental, human and epidemiological studies associating testosterone increase with neurological and neurodevelopmental effects (Qi et al., 2018; Nakano et al., 2010; Hines, 2003; Schwarz et al., 2011). Other authors link testosterone stimulation with apical effects associated with overexpression of androgens (Hotchkiss et al., 2007; Martin et al., 1998).…”
Section: Annex B – Assessment Of Non‐monotonicity Reported For Phthal...mentioning
confidence: 99%